BOTTOM-UP DEVELOPMENT MODEL İN RURAL DEVELOPMENT: THE CASE OF SENİRKENT WEAVERS COOPERATİVE (1931-2000) (Third Sector Social Economic Review, 2024)
Rural areas are often the most socioeconomically backward parts of a country. Particularly those areas that are not located on the main road routes tend to develop later due to the disadvantages of their geographical location. Cooperatives are an effective tool for the development of these regions. Before the planned development period, the people of Senirkent developed projects through the weavers' cooperative without receiving much state support. It found a market for the fabrics and carpets woven by its members and provided the inputs of the weavings cheaply. It worked almost like a state by carrying out planned and organized activities for the educational, economic, health and social development of its partners and local people.Weaving is predominantly a work done with women's labor. In Senirkent, although male labor was used in fabric weaving or carpet production, women were more involved in the weaving process during childhood, adolescence and adulthood.The aim of the research is to reveal the impact of the ""bottom-up development model"", which was put into practice with the first organization established in Senirkent in 1931 in the field of weaving, on the rural areas. In this context, the effects of the Weavers Cooperative established in Senirkent district center on the economic, educational, health and social development of the local people were investigated.Qualitative research method was adopted in the study and the participants were reached by snowball sampling. The data were obtained by asking open-ended interview questions prepared on the subject to 11 people in individual interviews and 8 people in focus group interviews, and by reviewing the relevant literature and archival documents.
Keywords: Senirkent; Rural Development; Collective Movements; M. Kemal Cabıoglu; Weavers Cooperative